Pengaruh Kompetensi Perangkat Desa, Komitmen Organisasi dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Gianyar Kabupaten Gianyar - Maharani, Ida Ayu Metha; Kusumawati, Ni Putu Ayu; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2025)
The distrct/city Regionial Revenuoe and Expenmditure Budgdet transfers villlage funds from the State Revenue and Expenditure Budget so that they can be used in the villages. Because the distribution of the budget increases annually, the village administration in Gianyar District has to be held responsible for the management of local funds. In order to ascertain the impact of organizational commitment, intrenal countrol sytems, and local apparatus competency on the accuntability of villaege fund managenment in Gianyar district, Gianyar Region, the Gianyar District Local Government undertook. Utilizing intentional examining was utilized to get the review's example size of 96. The study's findings demonstrate how village fund management duties are favorably and significantly impacted by internal control systems, organizational commitment, and local apparatus competency. It is hoped that village parties in Gianyar District will be able to further their understanding of financial management in the future in light of the research's findings by adhering to socialization, obtaining information from a variety of sources, and—of course—ensuring that increased accountability is balanced with the use of adequate information systems.